The Implementation of Diversion for Child Perpetrator in Magelang - Listiaratsany, Raihanida Putri; Astuti, Laras (Universitas Muhammadiyah Yogyakarta, 2024)
The increasingly high and diverse level of child delinquency is motivated by factors that making regulations of Children in Conflict with the Law must develop. One form of its development is the emergence of diversion, regulated in the Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Diversion must be pursued in 3 stages of justice: Investigation Stage, Prosecution Stage, and Examination Stage. The implementation of Diversion also exists in Magelang City. The objective of research is to find out how the implementation of Diversion in Children as Perpetrators in the City of Magelang and to find out the obstacles during the implementation. This research used normative-empirical legal method. The results show that the implementation of Diversion at each stage according to the data in the last 5 years is dominated by successful Diversion in accordance with the Juvenile Criminal Justice System, but it cannot be separated from obstacles that happen. These obstacles are the difficulty of forgiveness from both parties, the existence of an unfavorable relationship between the Victim and the Perpetrator, the compensation request are too high, and parents who do not want to be the guarantor of their child.